Concepts of understanding the essence of the “abuse of rights” category - V. V. Lazariev (Law and Safety)
The research is devoted to defining the essence of the abuse of rights and highlighting the main concepts for understanding this category. It has been emphasized that in the legal literature the issue of the abuse of rights is considered ambiguously, and the publication authors have different opinions on this subject. There is a view that the very term “abuse of rights” is controversial. Approaches to understanding the essence of the category of “abuse of rights” are divided into two broad groups depending on the theory of right origin that is used to study this manifestation. Thus, supporters of the natural law theory consider the abuse of rights as a certain ethical minimum of a subject's behaviour, which allows him or her to commit certain actions for which he or she will not be held legally liable. Supporters of the positivist theory generally deny the existence of the category of “abuse of rights” because there is no clear definition of this concept at the regulatory level.